PERENCANAAN DAN PENGENDALIAN PROGRAM MARKOMBUR DI TVRI SUMATERA UTARA - Azmiar Nasution; Sari Muliyani; Alphy Shahri Maulana; Fatur Rizky Silvana (Universitas Katolik Widya Karya Malang, 2023)
This study aims to find out how the Planning and Control of the Markombur Program at TVRI North Sumatra, this research uses qualitative methods, namely by observation to direct interviews at the research location. TVRI no longer fully uses conventional media but has utilized various online media such as YouTube, Twitter, Instagram, and others. By utilizing this media, the program is more attractive to viewers who have implemented a shift in technology. For this reason, this study discusses starting from production planning, program control, to production stages.